Effect of novel eco-friendly coating and packaging on quality and shelf life of Khasi mandarin (Citrus reticulata Blanco) - Theunuo, Kekhriezhau; Sema, Akali; Sarkar, Animesh (Journal of Postharvest Technology, 2023)
Khasi mandarin is commercially grown in northeast India and has enormous export potential. However, inadequate storage structures and  handling units with poor transport connectivity in the region are major setbacks to satisfy the growing demands. The experiment was  conducted at Nagaland University, Medziphema campus, to study effect of coating and packaging on quality and shelf life of khasi mandarin  fruits packed in T0: (Control), T1: (Aloe vera gel + Brown paper bag), T2: (Aloe vera gel +Aluminium container), T3: (Aloe vera gel + Cling wrap),  T4: (Aloe vera gel + Cardboard box), T5: (Aloe vera gel + Polythene bag), T6: (Coconut oil + Brown paper bag), T7: (Coconut oil + Aluminium  container), T8: (Coconut oil + Cling wrap), T9: (Coconut oil + Cardboard box and T10: (Coconut oil + Polythene bag) following CRD with three  replications. Treatments were analysed at every 5 days interval stored at ambient temperature for 50 days. Coconut oil + Cling wrap (T8)  showed the minimum PLW (7.25%), maximum shelf life (70days) and maintained the biochemical properties like TSS (11.50o Brix), titratable  acidity (0.71%), total sugar (7.37%) and ascorbic acid (32.27mg/100g pulp) throughout storage period. This might be a potential pathway for  edible and eco-friendly coating that can be used diversely in the field of postharvest shelf-life extension with minimal losses in quality.
Keywords: Khasi mandarin; Coating; Packaging; Quality,; Shelf life